STRENGTHENING FINANCIAL GROWTH THROUGH FULL COSTING IMPLEMENTATION AND SALES MONITORING: A CASE STUDY ON BRICK MSME IN SUPPORTING SDGS 9 - Widiya Wulandari; Annio Indah Lestari Nasution; Laylan Syafina (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2026)
This study aims to analyze the implementation of the full costing method and sales monitoring practices and their implications for the financial growth of brick businesses in supporting the achievement of Sustainable Development Goals (SDGs) 9: Industry, Innovation, and Infrastructure. The study used a qualitative approach with an explanatory case study at the Jaya Family Brick Business in Karang Anyar Village, Serdang Bedagai Regency. Data were obtained through direct observation, in-depth interviews with the owner and core workers, and documentation of cost and sales records. The results showed that before the implementation of full costing, the calculation of the cost of goods manufactured was carried out simply and did not include all overhead cost components, especially the maintenance costs of production assets. After the calculation using the full costing method, the cost of goods manufactured increased from Rp251 to Rp258 per unit, which reflects the real cost conditions of the business. These findings indicate that the full costing method is able to provide more accurate cost information as a basis for determining selling prices and controlling profit margins. In addition, the practice of sales monitoring, which is still administrative and manual, has not been optimally utilized as a strategic decision-making tool, especially in controlling receivables, production planning, and inventory management. The integration of full costing-based costing and structured sales monitoring has proven crucial in strengthening financial control and supporting sustainable business growth. This study confirms that strengthening cost and sales management in traditional production MSMEs is a strategic step in increasing the competitiveness of small-scale industries and supporting the achievement of SDG 9